Penyalahgunaan Perbincangan Interaktif dalam Aplikasi Bigo Live sebagai Media Komunikasi yang Bermuatan Tindak Pidana Pornografi - Kadek Indra Prayogi; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Jurnal Preferensi Hukum, 2021)
Developments in Information Technology have contributed greatly to the evolution of the world. The era also influences the lifestyle of people, including crime, for example, the pornography crime in Bigo Live. The problems are I) How is the legal arrangement for interactive conversations in the Bigo live application in relation to the enactment of the pornography law? and 2) What is the punishment for misuse of the Bigolive application as a media communication that contains pornography? The purpose of this research is to find out the legal arrangements for the crime of pornography in the Bigo live application in Indonesia as well as to find out criminal sanctions against criminal acts of misusing the Bigo live. The method used is the normative method. The statutory regulations that are used as references in solving criminal cases of abuse of the Bigo live application are article 282 paragraph (I) of the Criminal Code, the !TE Law in article 27 paragraph (I) jo 45 paragraph (I), and 4 paragraph (I), 29, 31, and 32 in Pornography Law.